FAKTOR-FAKTOR YANG MEMPENGARUHI TINDAKAN MASYARAKAT DALAM MEMBUANG SAMPAH RUMAH TANGGA DI DANAU SINGKARAK - Trisfa Augia; Lucy Akhila; Fitriyani (Poltekkes Kemenkes Surabaya, 2023)
Household waste is waste that comes from daily activities in the household. Garbage can cause environmental damage, a source of disease, and disrupt public health. Many rersidents of Jorong Ombilin live on the outskirts of Lake Singkarak and there are many community actions that dispose of household waste around the lake. This study aims to determine the factors that influence people's behavior in disposing of household waste in Lake Singkarak Jorong Ombilin in 2022. This research is a quantitative study with a cross-sectional design, which was conducted from February - September 2022 with a total sample of 90 respondents in Jorong Ombilin. Sampling using systematic random sampling technique. Data were processed using SPSS and analyzed using the chi square statistical test. The results showed that 67.8% of respondents took action to dispose of household waste in the lake, 58.9% had low level of education, 68.9% had bad knowledge, 56.7% had inadequate facilities, and 70.0% assume had inappropriate supervision. There is a correlation of variables of education (p=0.011), knowledge (p=0.000), availability of facilities (p=0.000), supervision (p=0.018) with community actions. Factors that have a significant relationship with community actions in disposing of household waste in Lake Singkarak Ombilin are the level of education, knowledge, availability of facilities, and supervision. It is recommended that the local government improve supervision of community actions and providing supporting facilities, create written regulation, and impose penalty of community actions in disposing of household waste.